Evaluación técnica y financiera de la implementación de un sistema de Bombeo Mecánico con Unidad Hidráulica Offshore en el Pozo 13 del Campo Trintes (2018)
The development of these proyect will be done of defining the main generalities of Trintes Field, where, is located the Well 13, it will describe the most important geological topics of the Field, as well as, the artificial lifts used then and now. On the other hand, there will be described the principal parameters of operation of the above mentioned equipments and his most frequent problems. The technical validation method will be through a comparative matrix between the Electrical Submersible Pump system, and the Offshore Mechanical Hydraulic Pumping Unit, where, it will be defined the main operational factors for each equipment and then determine the best option. Finally, it will be calculate the financial viability of the implementation of the Offshore Mechanical Hydraulic Pumping Unit defining the generated earnings for the project, as well as, the capital expenditures (CAPEX) and also the operative expenditures (OPEX) and then through a cash flow calculate the Net Present Value (NPV) and the Internal Rate of Return (IRR).